Implementasi Sistem Pengendalian Manajemen dan Kinerja Melalui Balance Scorecard - Ujang Cepi Barlian; Eliyanto , (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2019)
This study aims to reveal the implementation of control systems management through Balanced Scorecard Analysis, through the control system structure management, and through the management control system processes. That approach used in this research is explanative research. Design analysis for testing the hypothesis is done by testing simultaneously using Simple Regression analysis technique. The results of data processing through statistical analysis with a simple regression analysis with the processing steps referred to above and after going through detailed testing with a significance test, then it is made a discussion as a basis for making conclusions on the results research conducted. This study shows two findings. First, System Management control is very influential on organizational performance. Second, BSC very necessary in the management system in both government and non-governmental organizations government/private.